Moderators of the Effectiveness of a Web‐Based Tailored Intervention Promoting Physical Activity in Adolescents: The HELENA Activ‐O‐Meter. (11th March 2014) - Cook, Tina L.; De Bourdeaudhuij, Ilse; Maes, Lea; Haerens, Leen; Grammatikaki, Evangelia; Widhalm, Kurt; Kwak, Lydia; Plada, Maria; Moreno, Luis A.; Zampelas, Antonis; Tountas, Yannis; Manios, Yannis
ABSTRACT BACKGROUND The aim of this study was to examine the moderation effects of sex, age, and psychosocial determinants (intention, social support, and modeling) of physical activity (PA) in the relationship between an Internet‐based computer‐tailored intervention program (Activ‐O‐Meter) and modes of PA and commuting. METHODS The Activ‐O‐Meter with intervention and control condition was delivered to 555 adolescents (boys 50.5%, mean age: 14.4 years) in 6 European cities. Data on different modes of PA and commuting, sex, age, and psychosocial determinants were collected at baseline and at 3‐months follow‐up, using questionnaires. The moderation effects of psychosocial determinants, sex, and age on the association between condition and modes of PA and commuting were tested with linear regression. RESULTS Moderation analysis showed that the following increased adolescents' responsiveness to the intervention: male sex, older age, higher baseline intention to increase PA, higher perceived social support or modeling level by siblings, and low perceived social support by friends. CONCLUSIONS These findings should be taken into consideration when planning PA interventions in adolescents. Future intervention studies should also include moderation analysis in order to get a deeper understanding of why interventions are not effective for certain individuals and how this unresponsiveness could be overcome.